Diseño e implementación de un prototipo de calidad de servicio (QOS) sobre IPV6 - López Casa, Blanca Alejandra (2016)
The demand for the creation of new applications and the internet overuse have exposed the problems and limitations that the creators of IPv4 protocol not provided in their original design, mainly regarding to the quality service, consequently it has been proposed designing a prototype of Quality Service but now about the IPv6 protocol. In the present study, the respective comparative analysis of the main parameters of quality service between both IPv4 and IPv6 protocols were made. Therefore, was implemented a test site in which voice traffic, data and priority data were injected to observe the improvements or problems that develop with the measured parameters by injecting the three streams simultaneously and in an unidirectional way, this same procedure was performed for both IPv4 to IPv6 with and without QoS (quality of service), with tests and data obtained, it was proceeded to the respective analysis of results through comparative graphs. Once completed this analysis, the results obtained show that for IPv6 protocol, data streams have a lower delay compared with IPv4 protocol, but the packet loss in the IPv6 protocol without quality service flow is higher for the voice stream, these results should be mainly to the change of the size of the IPv4 header, which measures only 20 bytes unlike IPv6 having 40 bytes.